2001
DOI: 10.1007/s003300100994
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of abdominal tuberculosis

Abstract: The concept of "abdominal tuberculosis" in this review refers to peritoneum and its reflections, gastrointestinal tract, abdominal lymphatic system, and solid visceral organs, as they are subject to varying degrees of involvement alone or in combination. Some features, including free or loculated ascites with thin-mobile septa, smooth peritoneal thickening and enhancement, misty mesentery with large lymph nodes, smudged omental involvement, and advanced ileocecal changes demonstrated by US, CT, or gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
122
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 63 publications
2
122
0
7
Order By: Relevance
“…It is usually diagnosed late due to its nonspecific clinical presentation [6]. Approximately 15% -25% of cases with abdominal TB have concomitant pulmonary tuberculosis [7]. Hence, it is quite important in identifying these lesions with high index of suspicion especially in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually diagnosed late due to its nonspecific clinical presentation [6]. Approximately 15% -25% of cases with abdominal TB have concomitant pulmonary tuberculosis [7]. Hence, it is quite important in identifying these lesions with high index of suspicion especially in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculous lesions are associated with a variable spectrum of medical imaging manifestations, and they may mimic other diseases (6)(7)(8)(9). It is important to familiarize with the CT manifestations of tuberculous lesions to ensure accurate CT diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small proportion of patients with abdominal TB also suffer from pulmonary TB (7). It has been reported that multifocal TB may occur secondary to lympho-hematogenous dissemination after the initial infection (10).…”
Section: Discussionmentioning
confidence: 99%
“…Macronoduler hepatic tuberculomas, which measure more than a few centimeters, are rare. The lesions can be single or multiple [5,[7][8][9]. The US appearance of the lesions is hypoechoic or rarely hyperechoic.…”
Section: Discussionmentioning
confidence: 99%